EFEKTIFITAS MANAJEMEN PENDIDIKAN KARAKTER BERBASIS KEARIFAN LOKAL TERHADAP PENGEMBANGAN KARAKTER SISWA - Nurfaizah, Siti; Zulfia, Shofy; Agnestia, Rima (Jurnal Ilmiah Pendidikan dan Keislaman, 2023)
Character education in a place of study must involve all indicators (educational actors), including parts of education itself, namely teaching content, study procedures and assessment, management or administration of teaching. Indonesia seems to have lost local wisdom that has built character for centuries, such as fights between students and acts of corruption in all regions and institutions. Public lies that have become a habit do not have legal certainty because our laws can be bought and sold, even this country lacks figures who can be concrete models for society to emulate. Public concern for the development of national character is also a concern of the government. To improve national character education, various investments have been made in various places and various government agencies, especially in various units of the Ministry of Education. Development work is related to various levels and educational pathways, but not yet comprehensive. The community's desire and the government's concern for national character education then accumulates in the government's cultural and national character education policies and becomes one of the government's flagship programs for at least the next 5 (five) years. The application of Indonesian character education is not independent, but integrated with existing teaching by incorporating components of Indonesian character and culture. Indonesian education which increases technical knowledge based on the components of Pancasila, because it is not appropriate, only emphasizes one point of view of knowledge and values. Character education carried out in places of study is based on a political component originating from society, which requires the participation of all indicators (stakeholders), including parts of education itself, namely curriculum content, study procedures and evaluation, quality relations, administration or teaching management